Hemoglobin Level Examination in Students of Panrita Husada Bulukumba Health College Who Consume Instant Noodles - Hasanuddin, AR Pratiwi; Rifky , Andi Aidar; Fatimah, Fatimah (CV. Science Tech Group, 2024)
Hemoglobin is an iron-rich protein in red blood cells responsible for oxygen transport from the lungs to body tissues. Iron, along with vitamin B12 and folic acid, is essential for hemoglobin formation, with iron being a key component in heme production. Consuming instant noodles more than twice a week can increase the risk of metabolic disorders, such as obesity, high blood pressure, elevated blood sugar, and cholesterol. This study aimed to assess the hemoglobin levels of STIKES Panrita Husada Bulukumba students who consume instant noodles regularly. A descriptive cross-sectional quantitative study was conducted with 25 respondents. The results revealed a range of hemoglobin levels, with a low value of 8.0 g/dl, a normal value of 13.1 g/dl, and a high value of 16.1 g/dl, with a standard deviation of 2.04. The study found significant variation in hemoglobin levels among the students, with some indicating potential anemia and others suggesting polycythemia. This supports previous studies linking regular instant noodle consumption to malnutrition, particularly iron deficiency anemia.